Blinatumomab vs historical standard therapy of adult relapsed/refractory acute lymphoblastic leukemia - Gökbuget, N; Kelsh, M; Chia, V; Advani, A; Bassan, R; Dombret, H; Doubek, M; Fielding, A K; Giebel, S; Haddad, V; Hoelzer, D; Holland, C; et al. (Blood cancer journal, 2016)
We compared outcomes from a single-arm study of blinatumomab in adult patients with B-precursor Ph-negative relapsed/refractory acute lymphoblastic leukemia (R/R ALL) with a historical data set from Europe and the United States. Estimates of complete remission (CR) and overall survival (OS) were weighted by the frequency distribution of prognostic factors in the blinatumomab trial. Outcomes were also compared between the trial and historical data using propensity score methods. The historical cohort included 694 patients with CR data and 1112 patients with OS data compared with 189 patients with CR and survival data in the blinatumomab trial. The weighted analysis revealed a CR rate of 24% (95% CI: 20-27%) and a median OS of 3.3 months (95% CI: 2.8-3.6) in the historical cohort compared with a CR/CRh rate of 43% (95% CI: 36-50%) and a median OS of 6.1 months (95% CI: 4.2-7.5) in the blinatumomab trial. Propensity score analysis estimated increased odds of CR/CRh (OR=2.68, 95% CI: 1.67-4.31) and improved OS (HR=0.536, 95% CI: 0.394-0.730) with blinatumomab. The analysis demonstrates the application of different study designs and statistical methods to compare novel therapies for R/R ALL with historical data.